"Defining the relationship" in adolescent and young adult romantic relationships. (July 2020) - Knopp, Kayla; Rhoades, Galena K.; Stanley, Scott M.; Markman, Howard J.
"Defining the relationship" (DTR) conversations are a topic of interest among lay people, yet have been the focus of little empirical research, leaving a gap in the psychological literature on romantic relationship development. This article presents descriptive data from two studies about the characteristics and correlates of DTR talks in adolescents' and emerging adults' romantic relationships. In Study 1, DTR talks were found to occur in over half of the young adult participants' ( N = 341) most recent relationships, often involved discussion about aspects of commitment and sexual decisions, and occurred more often in relationships that were more serious, involved sex, delayed sex, and involved infidelity. Study 2 extended these findings to an online sample of 15- to 17-year-old adolescents ( N = 248) and found similar results. Further, Study 2 showed that DTR talks were associated with more frequent condom and birth control use. Qualitative data from Study 2 indicated that planning for the future and resolving ambiguity were common motivations for DTR talks, though many teens also reported more spontaneous motivations; further, DTR talks often, but not always, resulted in positive changes in the relationship, including increased clarity, intimacy, and commitment. These findings suggest that DTR talks are an important topic for future research and may have implications for young people's relationship quality and sexual health.